Electrical investigation on Eu+3 - doped copolymer composite system and conventional kinetic analysis - Pihtili, Guzin; Biryan, Fatih (Elsevier, 2021)
Poly(maleic anhydride-co-benzyl methacrylate) copolymer was prepared by using free radical polymerization (FRP) method at 70 degrees C. The structural characterization of the polymer was accomplished FT-IR, H-1 and C-13 NMR spectroscopic techniques. P(MA-co-BMA)/EuCl3 composites were prepared rate of 2%, 5% and 10% (wt/wt). The thermal behavior of pure copolymer was investigated by thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC). Thermal decomposition kinetics of poly(MA-co-BMA) carried out from Flynn-Wall-Ozawa method via TG curves for calculated apparent activation energies. According to FWO; the activation energy (E-a) was estimated as; 185.61 kJ/mol. Dielectric and electrical properties of copolymer/composite systems were investigated against frequency (range from 100 Hz to 20 kHz) at room temperature by using an impedance analyzer. The effect of EuCl3 concentration on dielectric constant, dielectric loss factors, ac conductivity, susceptance (B) and impedance (Z) was investigated. A remarkable increase was observed in dielectric and AC electrical properties were observed with the addition of Eu+3 to the polymer matrix. The B and Z parameters of poly(MA-co-BMA) and composites were investigated depending on frequency at room temperature based on the alternating current (AC). (C) 2020 Elsevier B.V. All rights reserved.
Keywords: EuCl3 composite; Electrical properties; Thermal kinetic; Synthesis